Pronounced Enhancement in Radiosensitization of Esophagus Cancer Cultivated in Docosahexaenoic Acid via the PPAR -γ Activation - Yang, Ying; Xu, Ying; Zhao, Congzhao; Zhang, Lirong; Nuerbol, Aslibek; Wang, Lili; Jiao, Yang (Frontiers in Medicine, 2022)
Docosahexaenoic acid (DHA) has been reported to suppress the tumor growth and improve prognosis and has been used to cooperate with many other chemotherapy medicines. Up to now, surveys focused on the Interaction between DHA and radiation are relatively modest. Our study sought to evaluate the radiosensitivity changes caused by DHA on esophageal cancer cells. We selected TE-1 and TE-10 esophagus cancer cells as models and performed routine cell proliferation assay and cloning assay to detect the impact of DHA combined with X-ray. We used cell cycle assay, lipid peroxidation assay, comet assay, and apoptosis assay to unearth the potential causes. We also launched a mouse transplanted tumor experiment to verify the synergetic effect of DHA and irradiation. Finally, a western blot assay was used to find a novel mechanism. As a result, DHA improved TE-1 and TE-10 radiosensitivity in vivo and in vitro. What's more, PPAR-γ expression increased due to the DHA supplement. Inhibiting PPAR-γ could attenuate benefits brought out by DHA somehow. Due to its explicit usage and convenience, DHA would serve as an adjuvant therapy before radiotherapy if the clinical trials indicated positive.